Mortality associated with timing of admission to and discharge from ICU: a retrospective cohort study - Laupland Kevin B; Misset Benoit; Souweine Bertrand; Tabah Alexis; Azoulay Elie; Goldgran-Toledano Dany; Dumenil Anne-Sylvie; Vésin Aurélien; Jamali Samir; Kallel Hatem; Clec'h Christophe; Darmon Michael; et al. (BMC, 2011)
Abstract Background Although the association between mortality and admission to intensive care units (ICU) in the "after hours" (weekends and nights) has been the topic of extensive investigation, the timing of discharge from ICU and outcome has been less well investigated. The objective of this study was to assess effect of timing of admission to and discharge from ICUs and subsequent risk for death. Methods Adults (≥18 years) admitted to French ICUs participating in Outcomerea between January 2006 and November 2010 were included. Results Among the 7,380 patients included, 61% (4,481) were male, the median age was 62 (IQR, 49-75) years, and the median SAPS II score was 40 (IQR, 28-56). Admissions to ICU occurred during weekends (Saturday and Sunday) in 1,708 (23%) cases, during the night (18:00-07:59) in 3,855 (52%), and on nights and/or weekends in 4,659 (63%) cases. Among 5,992 survivors to ICU discharge, 903 (15%) were discharged on weekends, 659 (11%) at night, and 1,434 (24%) on nights and/or weekends. After controlling for a number of co-variates using logistic regression analysis, admission during the after hours was not associated with an increased risk for death. However, patients discharged from ICU on nights were at higher adjusted risk (odds ratio, 1.54; 95% confidence interval, 1.12-2.11) for death. Conclusions In this study, ICU discharge at night but not admission was associated with a significant increased risk for death. Further studies are needed to examine whether minimizing night time discharges from ICU may improve outcome.